2013
DOI: 10.1021/bc4004266
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalized Gadolinium-Containing Prussian Blue Nanoparticles as Multimodal Molecular Imaging Agents

Abstract: Molecular imaging agents enable the visualization of phenomena with cellular and subcellular level resolutions and therefore have enormous potential in improving disease diagnosis and therapy assessment. In this article, we describe the synthesis, characterization, and demonstration of core-shell, biofunctionalized, gadolinium-containing Prussian blue nanoparticles as multimodal molecular imaging agents. Our multimodal nanoparticles combine the advantages of MRI and fluorescence. The core of our nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 38 publications
1
60
0
Order By: Relevance
“…Finally, studies conducted to calculate the photothermal conversion efficiency ( Figure 4D) demonstrated that the nanoparticles had a photothermal conversion efficiency of 16.1%, which is consistent with the previously determined photothermal conversion efficiency of Prussian blue nanoparticles (around 20%) 35 despite others). 32,38,39 Similarly, T2W scans demonstrated that the Fe 3 O 4 @GdPB nanoparticles generated increased contrast in a concentration-dependent manner ( Figure 3B), ie, increased darkening with increasing concentrations, similar to Fe 3 O 4 nanoparticles, which have been well-described in the literature. 5,6 Based on image processing of multiple T1W and T2W scans, we generated relaxation time plots as a function of the contrast agent, namely Gd 3+ ions for GdPB ( Figure 3C) and Fe 3 O 4 @GdPB ( Figure 3D), and Fe for Fe 3 O 4 ( Figure 3E) and Fe 3 O 4 @GdPB ( Figure 3F).…”
Section: Fe 3 O 4 @Gdpb Nanoparticles Function As Effective Ptt Agentssupporting
confidence: 77%
See 1 more Smart Citation
“…Finally, studies conducted to calculate the photothermal conversion efficiency ( Figure 4D) demonstrated that the nanoparticles had a photothermal conversion efficiency of 16.1%, which is consistent with the previously determined photothermal conversion efficiency of Prussian blue nanoparticles (around 20%) 35 despite others). 32,38,39 Similarly, T2W scans demonstrated that the Fe 3 O 4 @GdPB nanoparticles generated increased contrast in a concentration-dependent manner ( Figure 3B), ie, increased darkening with increasing concentrations, similar to Fe 3 O 4 nanoparticles, which have been well-described in the literature. 5,6 Based on image processing of multiple T1W and T2W scans, we generated relaxation time plots as a function of the contrast agent, namely Gd 3+ ions for GdPB ( Figure 3C) and Fe 3 O 4 @GdPB ( Figure 3D), and Fe for Fe 3 O 4 ( Figure 3E) and Fe 3 O 4 @GdPB ( Figure 3F).…”
Section: Fe 3 O 4 @Gdpb Nanoparticles Function As Effective Ptt Agentssupporting
confidence: 77%
“…The size (hydrodynamic diameter) and charge (zeta potential) distributions of the Fe 3 O 4 @GdPB nanoparticles were compared with both Fe 3 O 4 and GdPB nanoparticles (previously synthesized by us) 32,33 using dynamic light scattering on a Zetasizer Nano ZS (Malvern Instruments, Malvern, UK). Multiday stability of the Fe 3 O 4 @GdPB nanoparticles in ultrapure water was assessed by measuring their hydrodynamic size distributions every 24 hours over 5 days using dynamic light scattering.…”
Section: Characterization Of the Fe 3 O 4 @Gdpb Nanoparticlesmentioning
confidence: 99%
“…The clinically used T 1 contrast agent, Magnevist (gadolinium diethylenetriamine pentaacetic acid, Bayer HealthCare Pharmaceuticals Inc.), has an r 1 value of 4.3 mM − 1 s − 1 , which is higher than our PB-BSA nanoparticle [35]. But, recent studies suggested the longitudinal relaxivity of PB nanoparticles can be easily enhanced by doping with paramagnetic ions such as gadolinium (Gd 3+ ) or manganese (Mn 2+ ) [40][41][42].…”
Section: Longitudinal (T 1 ) Relaxivity Analysismentioning
confidence: 90%
“…Therefore, many groups including ours have explored the applications of PB-based nanoagents as PTT agent for cancer treatment in animal models [20][21][22][23][24][25][26][27][28] . Further, it has been found that doping of other paramagnetic ions, such as Gd 3+ and Mn 2+ into PB could enhance its T1 contrasting ability in magnetic resonance (MR) imaging [29][30][31][32][33][34] For in vitro cell toxicity assay, 4T1 cells were seeded in 96-well plates at a density of 10 4 Bio-RAD) to determine their relative cell viability. which was diluted into 10 ml by water, was measured by ICP-AES.…”
Section: Introductionmentioning
confidence: 99%